Is Urinary Interleukin-8 a Marker of Vesicoureteral Reflux in Children? - Seyedzadeh, Abolhassan; Eskandarifar, Alireza; Madani, Seyed Hamid; Amoori, Parisa; Soleimani, Akram (Journal of Pediatric Nephrology, 2013)
Introduction: Developing non-invasive but accurate methods to diagnose vesicoureteral reflux (VUR) is in progress. Cytokines, such as interleukin-8 (IL-8), are important mediators in inflammatory responses and are demonstrated to change during UTI and pyelonephritis, as well. Therefore, we attempted to evaluate the differences of IL-8 in children with UTI compared to children with and without VUR to assess if it can be hypothesized to be an appropriate diagnostic marker in children with VUR. Materials and Methods: We evaluated urine levels of IL-8 in 41 children aged 1 to 60 months who recovered from UTI for a minimum duration of 2-3 weeks. They were divided into 2groups: A and B (with and without VUR, respectively). Additionally, a group of normal children was considered as the control group (group C). Urine IL-8 levels were measured for the three groups and corrected for urine creatinine (Cr) (IL-8/Cr). Afterwards, they were compared using One-Way ANOVA test. Results: The mean IL-8/Cr level was 81.7 ± 90.1 in group A, 289.8±640.2 in group B, and 9.6 ± 12.2 in group C with no significant difference (p=0.056). Conclusions: Our finding suggests there is no significant difference in urine IL-8/Cr levels between patients with and without VUR and therefore, we cannot propose IL-8 as a diagnostic marker for VUR. Keywords: Interleukin-8; Pediatrics; Pyelonephritis; Urinary Tract Infections; Vesico-Ureteral Reflux.